Determinant of criminal activities by some Nigerians residing in Malaysia: A socio-economic perspective - Adeyemi, Adewale Abideen; Amuda, Yusuf Jelili; Abdul Razak, Dzuljastri; Mohamed, Kamil Naail; Olaniyi, Oladokun Nafiu (UPM Press, 2017)
Even when statistics from various international institutions indicate a relatively higher prevalence of crimes among the locals, the increasing trend of a spike in crime rates among immigrants especially of African descent in Malaysia is also bothersome. Given the rise in the number of reported criminal activities involving, specifically, Nigerians in Malaysia, it becomes necessary to understand the underlying motives for such behaviour as part of the attempt to arrest this trend. The current study explores the factors contributing to criminal behaviour among some Nigerians residing in Malaysia. In view of the prominence of socio-economic factors in explaining criminal behaviour, this study explores this rising phenomenon from a socio-economic perspective. In addressing this objective, this study employs the Analytical Hierarchy Process (AHP), whereby the socio-economic factors are ranked according to their contribution to the crime rate. It is expected that the findings of this study will shed light on the root causes of this menace, thereby offering policy makers greater information and insight with which to more effectively curb such criminal activities